2020
DOI: 10.1038/s41598-020-61826-1
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Seq transcriptome profiling in three liver regeneration models in rats: comparative analysis of partial hepatectomy, ALLPS, and PVL

Abstract: The liver is a unique organ that has a phenomenal capacity to regenerate after injury. Different surgical procedures, including partial hepatectomy (PH), intraoperative portal vein ligation (PVL), and associated liver partition and portal vein ligation for staged hepatectomy (ALPPS) show clinically distinct recovery patterns and regeneration. The observable clinical differences likely mirror some underlying variations in the patterns of gene activation and regeneration pathways. In this study, we provided a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…The DEGs were mapped to its corresponding gene object in the Ingenuity pathway knowledge base and gene interaction networks. A right-tailed Fisher’s exact test was used to calculate a p -value determining the probability that the biological function (or pathway) assigned to the data set is explained by chance alone ( Colak et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The DEGs were mapped to its corresponding gene object in the Ingenuity pathway knowledge base and gene interaction networks. A right-tailed Fisher’s exact test was used to calculate a p -value determining the probability that the biological function (or pathway) assigned to the data set is explained by chance alone ( Colak et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, RELA, E2F1, GABPB1, ETS2 regulons were active in hepatocytes from P14 and the initiation-progression stage of regeneration, but were turned off in adult hepatocytes and at the termination-rematuration stages (Figure 4C cluster I, 4D), This indicates that these regulons likely play dual roles in regulating the hepatocyte hyperplastic response -i.e., in normal liver development and following an injury in adult animals. In line with our results, previous studies have found that a rapid increase in the expression and/or DNA binding activity of NF-kB (RELA and RELB), E2Fs (E2F1, 3, 4, 6 and 8), AP-1 (JUN and FOS), POLE4, TRP53, MYC, CREM, and ETS (ETS2, GABPB1) family of transcription factors is involved in the initiation of stress signaling, oxidative stress, DNA replication/repair, and cellcycle entry at the early stages of liver regeneration (Baena et al, 2005;Beyer et al, 2008;Bhat et al, 1987;Chaisson et al, 2002;Colak et al, 2020;Iimuro et al, 1998;Inoue et al, 2002a;Kelley-Loughnane et al, 2002;Kurinna et al, 2013;Servillo et al, 1998;Sladky et al, 2020;Stepniak et al, 2006;Su et al, 2002;Westwick et al, 1995;Wu et al, 2013;Yang et al, 1991;Zellmer et al, 2010).…”
Section: Rewiring Of Gene Regulatory Network Activates Cell State Transitions During Regenerationmentioning
confidence: 99%
“…TRIzol ® reagent (Invitrogen, Carlsbad, CA, USA) was used for isolation of total RNA from liver tissue [ 59 ]. cDNA libraries were generated and purified using QuantSeq 3′ mRNA-Seq Library Prep Kit for Illumina (LEXOGEN, Vienna, Austria) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%